2016
DOI: 10.1063/1.4950749
|View full text |Cite
|
Sign up to set email alerts
|

Divalent cation shrinks DNA but inhibits its compaction with trivalent cation

Abstract: Our observation reveals the effects of divalent and trivalent cations on the higher-order structure of giant DNA (T4 DNA 166 kbp) by fluorescence microscopy. It was found that divalent cations, Mg(2+) and Ca(2+), inhibit DNA compaction induced by a trivalent cation, spermidine (SPD(3+)).On the other hand, in the absence of SPD(3+), divalent cations cause the shrinkage of DNA.As the control experiment, we have confirmed the minimum effect of monovalent cation, Na(+) on the DNA higher-order structure. We interpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 35 publications
2
24
0
Order By: Relevance
“…Our experiments were conducted in a simplified model system to focus on the action of polyamines on DNA. Further studies in the nonspecific but significant effect of polyamines on DNA and other negatively-charged biomolecules by taking into account the influence of cationic species [ 35 , 36 ] such as K + and Mg 2+ would provide useful insight regarding mechanisms of living matters as autonomous self-control system.…”
Section: Discussionmentioning
confidence: 99%
“…Our experiments were conducted in a simplified model system to focus on the action of polyamines on DNA. Further studies in the nonspecific but significant effect of polyamines on DNA and other negatively-charged biomolecules by taking into account the influence of cationic species [ 35 , 36 ] such as K + and Mg 2+ would provide useful insight regarding mechanisms of living matters as autonomous self-control system.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the compaction of long DNAs with polycations like polyamines (spermine and spermidine) and histone can be observed at the level of individual chains as a first-order phase transition, which is believed to be caused by the exchange of counter ions that have accumulated around DNAs (Takahashi et al 1997;Murayama and Yoshikawa 1999). The folding transition occurs essentially in an all-or-none (intermolecular) manner, i.e., each DNA molecule can assume a folded (compacted) or unfolded morphology depending on the polycation concentration (Takahashi et al 1997;Tongu et al 2016). Interestingly, the distance within which the phase transition can propagate along the chain can be modulated by the concentration ratio of polyvalent to mono-/di-valent salts, since a coexisting salt with a lower valency can alter the free energy of the system, or apparently shield electrostatic interaction by competing for binding sites on DNAs with polycations (Yoshikawa 2001).…”
Section: Simple Models For Chromosomes: Phase Behavior In a Single Dnmentioning
confidence: 99%
“…In classical Manning-Oosawa condensation theory, the fraction of counterions condensing on uniformly charged rod depends only on the valence of counterions, but is independent of other factors, such as type of ions, pH and ionic strength in solution [41]. When many types of counterions exist in solution, the electrostatic interaction between DNA and counterions becomes much more complicated than the case of single counterion [42,43,44,45,46,47]. It has been shown that increasing monovalent salt concentration hinders charge inversion by multivalent ions [10,48].…”
Section: Introductionmentioning
confidence: 99%